2006
DOI: 10.1177/1069072705282435
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Five Years of Self-Efficacy in Career Assessment and Practice

Abstract: In this article, the ways in which self-efficacy has influenced career assessment and practice during the past 25 years are explored. Focus is on research describing or evaluating specific theory-based interventions or programs with particular attention to experimental, quasi-experimental, and program evaluations studies published in refereed professional journals. Suggestions for further research and practice are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 84 publications
2
39
0
8
Order By: Relevance
“…This result is consistent with previous studies on interventions boosting career self-efficacy (Betz, 2007;Gainor, 2006) and career preparedness (Koivisto et al, 2010;Vuori & Vinokur, 2005). Considering the selfefficacy related propositions of general social cognitive theory (Bandura, 1977(Bandura, , 2006 and its application to career context (Lent et al, 1994), this may mean that participants' strengthened preparedness to make career choices as a result of the workshops may also have increased their investment of motivational resources in the exploitation of learned career exploration and planning skills outside of the workshop.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is consistent with previous studies on interventions boosting career self-efficacy (Betz, 2007;Gainor, 2006) and career preparedness (Koivisto et al, 2010;Vuori & Vinokur, 2005). Considering the selfefficacy related propositions of general social cognitive theory (Bandura, 1977(Bandura, , 2006 and its application to career context (Lent et al, 1994), this may mean that participants' strengthened preparedness to make career choices as a result of the workshops may also have increased their investment of motivational resources in the exploitation of learned career exploration and planning skills outside of the workshop.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, on the basis of SCCT (Lent et al, 1994) and the previous research on interventions aimed at boosting career self-efficacy (Betz, 2007;Gainor, 2006) and preparedness (Koivisto et al, 2010;Vuori & Vinokur, 2005), we suggest that social learning in the TWL intervention workshops increases career choice preparedness. In turn, in line with SCCT, we suggest that the effect of learning experiences in the workshops on career planning attitude is partly direct and partly mediated by the increase in career choice preparedness (Betz & Borgen, 2000;Fouad & Smith, 1996;Lent et al, 1994Lent et al, , 2005.…”
Section: Components Of Career Preparation As Amentioning
confidence: 91%
“…In the current study, we interpret self-efficacy more specifically as the belief of the actor that s/he has the capacity of being a successful student in the chosen scientific field, and thus as a potentially important factor to influence the intention to enter a research-oriented career. More in particular we use the notion of 'academic self-concept' (Bennett, 2009), to measure the extent to which someone believes he or she is successful as an academic student (Gainor, 2006;Dasan, 2013). The hypothesis is that students with a higher score on academic self-concept, will be more inclined to enter a research-oriented career.…”
Section: Variables and Hypothesesmentioning
confidence: 99%
“…The knowledge gained by investigating the learning environment and its role in math interest can help career, school, and mental health counselors, as well as educators and others who work with youth, understand the factors that influence early STEM career development. This, in turn, will allow for the development of research-based interventions to help girls and women gain greater representation in predominantly male STEM fields ( Gainor, 2006). These early learning experiences play a powerful and long-lasting role in girls' and women's math self efficacy and outcome expectations .…”
Section: Need For the Studymentioning
confidence: 99%
“…Analyzing 25 years of self-efficacy research, Gainor (2006) concluded that empirical studies support the use of seeT when designing, implementing, and evaluating interventions that can assist career choice and development. Betz and Hackett (2006) noted that some researchers appear to disregard the aspects of Bandura' s ( 1977Bandura' s ( a, 1977bBandura' s ( , 1986) Social Cognitive Theory, the theoretical foundation of SCCT.…”
Section: Math and Social Cognitive Career Theorymentioning
confidence: 99%